A COMPARATIVE STUDY ON WELLNESS LIFESTYLE OF MALES AND FEMALES OF HIGHER EDUCATION INSTITUTIONS IN DELHI: AN EXPLORATION ON GENDER DIFFERENCES - Malhotra, Himani; Malhotra, Richa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The term Wellness is a multifaceted notion that includes one’s state of mind, body, and social relationships. Delhi’s higher education institutions are multicultural and accommodate students from various racial and cultural backgrounds. The main aim of the present research endeavor is to examine current behavioral patterns and wellness lifestyle of males and females in higher education institutions in Delhi and identify any necessary amendments which are needed for long-term health and wellness. In the present research work, total numbers of 132 undergraduate students comprising of 63 males and 69 females of 17-21 age groups from various Higher Education Institutions in Delhi, have been randomly selected. There are nine variables namely 1) Health Related Fitness, 2) Nutrition, 3) Avoiding Chemical Dependency, 4) Stress Management, 5) Personal Hygiene/Health, 6) Disease Prevention, 7) Emotional Wellbeing, 8) Personal Safety, 9) Environmental Health & Protection etc which have been measured by the questionnaire namely "Wellness Lifestyle Questionnaire" (LQ) by Hoeger & Hoeger. Each questionnaire responses have been converted into scores from Always to Never (5 to 1). For analyzing the data, descriptive statistics have been employed :-mean, standard deviation and also percentage have been used to illustrate the data. Based on the findings, it has been concluded that Male students are excellent and good in variables like: - Health Related Fitness, Nutrition, Avoiding Chemical Dependency, Stress Management, Personal Hygiene/Health, Emotional Wellbeing but Male students need improvement in other variables such as: Disease Prevention, Personal Safety and Environmental Health & Protection. Whereas Female students found excellent and good in variables like: Nutrition, Avoiding Chemical Dependency, Stress Management, Personal Hygiene/Health, Emotional Wellbeing but Female students need improvement in other variables such as: Health Related Fitness, Disease Prevention, Personal Safety and Environmental Health & Protection.